Role of Oil Price in Fiscal Cyclicality in Saudi Arabia - Alkhateeb, Tarek Tawfik Yousef; Mahmood, Haider; Sultan, Zafar Ahmad (International Journal of Energy Economics and Policy, 2021)
Testing cyclicality of fiscal policy is pertinent in any country to observe its type of cyclicality with the business cycle. In the oil abundant economy, oil price and trade openness may also play a role in determining the fiscal policy cyclicality. This research probes the role of economic growth, trade openness, and oil price on government consumption growth to verify the type of cyclicality in Saudi Arabia from 1971 to 2018. The cointegration test of Pesaran (2001) is utilized to test the cyclicality hypothesis with augmented critical bound statistics developed by Kripfganz and Schneider (2019). We corroborate the long and short-run relationships in the fiscal model of Saudi Arabia. Further, procyclicality is proved in the long run and countercyclicality is corroborated in the short run with a one-year lag effect. Moreover, government revenue has a positive effect on expenditure. However, oil prices and trade openness could not affect government spending. Keywords: Fiscal Cyclicality, oil price, trade openness, government consumption, economic growth JEL Classifications: E62, Q41, P33, O43 DOI: https://doi.org/10.32479/ijeep.10700